Genetic Mutations of Tim-3 Ligand and Exhausted Tim-3+ CD8+ T Cells and Survival in Diffuse Large B Cell Lymphoma - Tingting Zhang; Tianyuan Ren; Zheng Song; Jing Zhao; Lei Jiao; Zhenzhen Zhang; Jin He; Xianming Liu; Lihua Qiu; Lanfang Li; Shiyong Zhou; Bin Meng; et al. (Journal of Immunology Research)
Tim-3 is a promising target for antitumor immunotherapy. A number of clinical trials are evaluating the efficacy of anti-Tim-3 therapies as a single agent or combinations in solid tumors and haematologic malignancies. However, there remains a considerable lack of data on Tim-3 signalling, especially the genetic characteristics and immune microenvironment, in diffuse large B cell lymphoma (DLBCL). Herein, we identified three genetic mutations in galectin-9, a major ligand of Tim-3, in six patients with DLBCL (6/188, 3.2%) that were not detected in the COSMIC database. The Oncomine database showed that the mRNA levels of Tim-3 were higher in DLBCL cells than those in normal B cells. Multiplexed immunofluorescence revealed that patients with Tim-3-expressing tumor-infiltrating lymphocytes (Tim-3+ TILs) exhibited poor outcomes than those with Tim-3- TILs (p=0.041). The median survival times of these patients were 65.0 (95% confidence interval (CI): 71.2–88.6) and 79.9 months (95% CI: 54.4–75.6), respectively. Furthermore, we defined a novel subtype of exhausted T cells, named as exhausted Tim-3+ CD8+ T cells, and found that patients with exhausted Tim-3+ CD8+ T cells (median survival, 62.8 months, 95% CI: 50.0–75.6) exhibited shorter survival than those with nonexhausted Tim-3- CD8+ T cells (median survival, 82.5 months, 95% CI: 72.0–92.9; p=0.034). Overall, these findings provide the genetic status of the Tim-3 ligand in DLBCL. Patients with Tim-3+ TILs and exhausted Tim-3+ CD8+ T cells exhibited inferior survival, thus highlighting the possibility of potential therapeutic applications of the inhibition of Tim-3 alone or in combination with other immune checkpoints for treatment of patients with DLBCL.